Calibration, Expected Utility and Local Optimality - Dean P. Foster; Rakesh V. Vohra (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
We propose a framework for reconciling frequentist and subjectivist views of probability. In an environment with repeated trails we show that beliefs about the possible states of nature can be represented by probabilities. Second, these probabilities will correspond to long run frequencies. In particular they will be naively calibrated. Third, the actions chosen in each trial will be the ones that maximize expected utility on that trial. The expectation is with respect to the probabilities used to represent beliefs.
Keywords: 330